Effects of fertilizer type and harvesting age on species composition, yield and chemical composition of natural pasture in the highlands of Ethiopia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Yalew S, Asmare B, Mekuriaw Y. 2020. Effects of fertilizer type and harvesting age on species composition, yield, and chemical composition of natural pasture in the highlands of Ethiopia. Biodiversitas 21: 4999-5007. The experiment was conducted to evaluate the effects of fertilizer type and harvesting age on species composition, yield, and chemical composition of natural pasture in the highlands of Ethiopia. The experiment was laid out in randomized complete block design with factorial arrangement of two factors (fertilizer and harvesting age) with five replications. The data collected from the current study were forage species composition, dry matter yield, and chemical composition of natural pasture at different ages of harvesting. Forage species composition was determined by taking representative samples and identifying species from each sampling site. The samples of natural pasture were harvested at 90 and 120 days of age, weighed, dried, and then ground after that subsamples were taken for analyses of dry matter (DM), crude protein (CP), ash, acid detergent fiber (ADF), neutral detergent fiber (NDF) and acid detergent lignin (ADL). All the collected data were subjected to GLM ANOVA procedures of SAS version 9.0. The result indicated that all species composition and dry matter yield were significantly affected (P
Keywords: Fertilization, feed quality, grazing land, highlands of Ethiopia